(untitled) (International Journal of Engineering and Computer Science, 2017)
Natural language is a study that involves the communication between humans and computers. There are number of tasks that can be performed by using NLP like speech recognition, information extraction, segmentation, language translation, grammer checking etc.. Punjabi language is mostly spoken by the people living in Punjab and Pakistan. NLP is considered as a hard problem in computer science due to the ambiguity of the languages .POS tagging involves process for disambiguating the part-of-speech information for such ambiguous words by taking into consideration the context information. In this paper we study this problem and generate “ automatic rule detection and pos tagging of Punjabi text” by using rule based approach. The chances of error are less and work is more efficient and accurate.